ADMINISTRASI DAN SUPERVISI PENDIDIKAN ISLAM MEDIA DIGITAL BERBASIS CINTA PADA MADRASAH IBTIDAIYAH - Ocha Azkiya Lutfiana; Rizki Sri Agustiana; Ahmad Zainuri; Frika Fatimah Zahra (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to analyze the role of Islamic education administration and supervision in the use of love-based digital media in the learning process at Madrasah Ibtidaiyah. Love-based digital media is understood as an educational technology approach that emphasizes values of compassion, empathy, respect, and positive communication between teachers and students. The study employs a qualitative approach with a case study design in several Madrasah Ibtidaiyah that have implemented the integration of Islamic values in digital media utilization for learning. Data were collected through observation, in-depth interviews, and documentation, and then analyzed using data reduction, presentation, and verification techniques. The findings reveal that Islamic education administration plays a crucial role in program planning, managing digital facilities, and formulating media usage regulations aligned with Islamic ethics and manners. Educational supervision is carried out through professional development of teachers, guidance in using digital platforms, and emphasizing teaching practices that highlight a love-based approach as part of Islamic pedagogical responsibility. The use of love-based digital media was found to enhance learning comfort, student discipline, and positive interactions between teachers and learners. The study recommends improving teachers’ digital competencies, providing adequate infrastructure, and implementing an Islamic supervision model that is responsive to 21st-century learning needs.